DESIGN ANALYSIS AND OPTIMIZATION OF CENTRIFUGAL BLOWER - Prof. Kshirsagar S.R; Mahesh Shinde; Shubham Nandgude (International Journal of Innovations in Engineering Research and Technology, 2021)
Blower is used to deliver the air or gas with an appreciable rise in pressure again the flow resistance. It is an important role in various industries for air-conditioning systems, furnaces and dust or fume extraction systems Based on the input data the design calculations has been carried out and modelled using SOLIDWORKS. The clean-up and meshing are carried out in CFD Analysis The Main Aim Behind these Project for increase energy efficiency & constant air flow delivery that enable them generate energy of up to 84% efficiency. Done the CFD investigation for getting improved parameter blend utilizing prepare. This will provide optimised design of centrifugal blower This paper gives the solution to above problems by optimization of centrifugal blower impeller by static and modal analysis using FEA for the materialMS.